PARENTS PREVENTIVE ACTIONS ON SEXUAL VIOLENCE IN EARLY CHILDREN - Mustika; Sam’un Mukramin (Media Inovasi Pendidikan dan Publikasi, 2023)
Cases of sexual violence against children are increasingly worrying, so parents have to be more vigilant about the safety of their children. So there is a need for efforts to prevent sexual violence in early childhood. This research discusses the importance of interpersonal communication between parents and children, especially those at an early age to gain an understanding of how to protect themselves. Communication is one of the solutions in preventing sexual violence that occurs in children, so it needs to be built from early childhood so that a good relationship between parents and children is created so that they can be open and harmonious with each other. Parents must have sufficient ability and knowledge to equip and protect children from evil that stalks children. This research was conducted by applying psychology in communication to make it easier for parents to prevent sex education, as well as to take countermeasures through warm and open communication.